If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -109 = 2x + 91 Reorder the terms: -109 + 4x = 2x + 91 Reorder the terms: -109 + 4x = 91 + 2x Solving -109 + 4x = 91 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -109 + 4x + -2x = 91 + 2x + -2x Combine like terms: 4x + -2x = 2x -109 + 2x = 91 + 2x + -2x Combine like terms: 2x + -2x = 0 -109 + 2x = 91 + 0 -109 + 2x = 91 Add '109' to each side of the equation. -109 + 109 + 2x = 91 + 109 Combine like terms: -109 + 109 = 0 0 + 2x = 91 + 109 2x = 91 + 109 Combine like terms: 91 + 109 = 200 2x = 200 Divide each side by '2'. x = 100 Simplifying x = 100
| 2(n+10)=-20 | | h-17=2 | | (12x+14)+(9x-2)=180 | | 5/6/3/4 | | 1/10(30-2x)=-1/15(2x+45) | | 5v^2+6=-17v | | 28=8h | | 75=.05x | | (1160*4)+(6*x)=52800 | | 15=.10x | | 4p+2=-10-7p | | 4640+(6*x)=52800 | | 5y(-7)=23-y | | 4640+6x=52800 | | 11-x=2x+7-3*(x+1) | | 1/2x+1/3y=28 | | 5y-7=23-y | | 60/x-38=48 | | 4(x-7)=4(x-7) | | 3/2h-1/3h+11=8 | | 2x^2+14=x+x^2+9x | | 3x+9=81+6x | | (4*x)+(6*x)=52800 | | 2x+12=3x-2 | | 4n=70 | | 12-2y=56 | | f(x)=5x+12 | | 9n+1=105 | | 1/3(3x-6)=2x | | 3*c=27 | | 6x^2-13=11 | | (2x-4)/3=(3x+4)/2 |